2011
DOI: 10.1371/journal.pone.0027069
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy, Effectiveness and Cost for Cognitive Impairment and Dementia Screening of Three Short Cognitive Tests Applicable to Illiterates

Abstract: BackgroundIlliteracy, a universal problem, limits the utilization of the most widely used short cognitive tests. Our objective was to assess and compare the effectiveness and cost for cognitive impairment (CI) and dementia (DEM) screening of three short cognitive tests applicable to illiterates.MethodsPhase III diagnostic test evaluation study was performed during one year in four Primary Care centers, prospectively including individuals with suspicion of CI or DEM. All underwent the Eurotest, Memory Alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 36 publications
1
24
1
1
Order By: Relevance
“…The Phototest does not require any reading abilities and does not include pencil and paper tasks, thus making it a good choice for use with this population. 10 Therefore, further studies with illiterates are required. The concurrent validity of the test was determined with the MoCA, and this may have biased this indicator because the neuropsychological test was also used to includeeexclude participants from the sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Phototest does not require any reading abilities and does not include pencil and paper tasks, thus making it a good choice for use with this population. 10 Therefore, further studies with illiterates are required. The concurrent validity of the test was determined with the MoCA, and this may have biased this indicator because the neuropsychological test was also used to includeeexclude participants from the sample.…”
Section: Discussionmentioning
confidence: 99%
“…The Phototest was developed in Spain and has proven high diagnostic accuracy and effectiveness for cognitive impairment and dementia, even when compared with more traditional screening tests such as the Mini-Mental State Examination 7e9 or the Memory Alteration Test. 10 It has been demonstrated that cutoff points of 26 and 28 offer satisfactory discriminant validity for Alzheimer's disease and cognitive impairment, respectively. 11 In addition, the test also has good testeretest and interobserver reliability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Mini-Cog was not a valid choice in the studied sample, and this result, which was consistent with previous research, advise against the use of the Mini-Cog, particularly in settings where the proportion of unrecognized dementia is low. In these settings, the use of tests that offer a wider range of tasks and score, yet maintaining acceptability and feasibility, seems more adequate [38]. In light of the relevance of the detection of CI, more human and technical resources should be implemented in PC.…”
Section: Discussionmentioning
confidence: 99%
“…El rendimiento diagnóstico global del AD8 es similar al mostrado en esta misma muestra por el Fototest (aROC 0,93, IC del 95%, 0,89–0,96; CC del 87,7%), un test cogni-tivo breve (< 3 min) aplicable a analfabetos y no influido por el nivel educativo 20 , que en nuestro medio ha mostrado una efectividad diagnóstica superior a la del MMSE 33 y mayor efi-ciencia que otros instrumentos aplicables a analfabetos 34 . Aunque la UD global es similar, para el mejor punto de corte (3/4) el AD8 es más sensible (S 0,93, IC del 95%, 0,88–0,96; E 0,81, IC del 95%, 0,72–0,88) en tanto que el Fototest (28/29) es más específico (S 0,83, IC del 95%, 0,77–0,88; E 0,96, IC del 95%, 0,89–0,99).…”
Section: Discussionunclassified